Consciousness and cognition : fragments of mind and brain - Cohen, Henri, 1945-; Stemmer, Brigitte (Academic Press, 2007)
What were the circumstances that led to the development of our cognitive abilities from a primitive hominid to an essentially modern human? The answer to this question is of profound importance to understanding our present nature. Since the steep path of our cognitive development is the attribute that most distinguishes humans from other mammals, this is also a quest to determine human origins. This collection of outstanding scientific problems and the revelation of the many ways they can be addressed indicates the scope of the field to be explored and reveals some avenues along which research is advancing. Distinguished scientists and researchers who have advanced the discussion of the mind and brain contribute state-of-the-art presentations of their field of expertise. Chapters offer speculative and provocative views on topics such as body, culture, evolution, feelings, genetics, history, humor, knowledge, language, machines, neuroanatomy, pathology, and perception. This book will appeal to researchers and students in cognitive neuroscience, experimental psychology, cognitive science, and philosophy. * Includes a contribution by Noam Chomsky, one of the most cited authors of our time.